GUT DYSBIOSIS IN THE ADENOMA-CARCINOMA SEQUENCE: A COMPREHENSIVE REVIEW OF CLINICAL AND PRECLINICAL EVIDENCE - Paulina Biedroń; Anna Skrzypek; Maciej Hutkowski; Mikołaj Zbrożek; Zuzanna Chwostek; Bartłomiej Kosiarski; Patrycja Markowicz; Hanna Maruchniak; Wiktoria Marzec; Krzysztof Biłyk (International Journal of Innovative Technologies in Social Science, 2026)
Background: Colorectal cancer (CRC) is a major oncological challenge increasingly linked to gut microbiota dysbiosis. Microbial alterations are believed to drive the progression from benign precursor lesions to invasive cancer along the adenoma-carcinoma sequence. Aim: The aim of this review is to summarize current knowledge about the role of microbial alterations in the adenoma-carcinoma sequence, focusing on specific pro-tumorigenic pathogens - specifically Fusobacterium nucleatum, enterotoxigenic Bacteroides fragilis (ETBF), and pks+ Escherichia coli and their pathogenic mechanisms. Material and methods: A literature review was conducted using PubMed and Google Scholar, focusing on articles published in English within the last eight years with a particular focus on recent evidence from 2019 to 2025. The search prioritized metagenomic analyses and preclinical studies regarding CRC, dysbiosis, and specific bacterial drivers using terms such as ‘colorectal cancer’, ‘adenoma-carcinoma sequence’, and ‘gut microbiota’. Results: Dysbiosis appears early in carcinogenesis, characterized by the depletion of beneficial butyrate-producers and expansion of pathobionts. Key pathogens drive tumorigenesis through distinct mechanisms, including toxin production (e.g., BFT, colibactin), DNA damage, and immune modulation. Functional evidence from murine models confirms a causal link, demonstrating that dysbiotic microbiota actively accelerates tumor growth and inflammation. Conclusions: Intestinal dysbiosis is a fundamental, early driver of CRC pathogenesis, not merely a passive consequence. Identifying oncogenic bacteria offers new perspectives for early non-invasive diagnosis and therapeutic strategies to inhibit disease progression.